Occupational physical activity, energy expenditure and 11-year progression of carotid atherosclerosis - Krause, Niklas; Brand, Richard J.; Kaplan, George A.; Kauhanen, Jussi; Malla, Smriti; Tuomainen, Tomi-Pekka; Salonen, Jukka T. (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'This study prospectively assessed the effects of occupational physical activity on atherosclerosis progression. ' ' METHODS ': 'This population-based prospective study of ultrasonographically assessed carotid intima media thickness (IMT) used repeated measures of occupational physical activity during baseline, 4-year, and 11-year examinations of 612 Finnish men 42–60 years of age at baseline. The association between five measures of energy expenditure and the 11-year change in maximum IMT was evaluated in regression models adjusting for 21 potential confounders, including biological factors, leisure-time physical activity, smoking, socioeconomic status, psychosocial job factors, and baseline health status. ' ' RESULTS ': 'At baseline, 31% of all the men and 51% of those with ischemic heart disease (IHD) exceeded the recommended maximum levels of relative aerobic strain. All five measures of energy expenditure were significantly associated with adjusted 11-year IMT change. Significant interactions were found between IHD and several measures of energy expenditure. Maximum relative aerobic strain resulted in a 90% increase in IMT among the men with IHD compared with a 46% increase among those without IHD. The men with preexisting carotid stenosis also had higher rates of IMT progression than the men without this condition. ' ' CONCLUSIONS ': 'This study shows that high energy expenditures at work are associated with an accelerated progression of atherosclerosis even after control for virtually all known cardiovascular risk factors, especially among older workers and workers with preexisting IHD or carotid artery stenosis. The findings support the hemodynamic theory of atherosclerosis and have important implications for workplace surveillance and disease prevention.
Keywords: behavioral factor; caloric job demand; cardiorespiratory fitness; cardiovascular disease; carotid atherosclerosis; coronary heart disease; energy expenditure; hemodynamic theory of atherosclerosis; occupational physical activity; physical workload; prospective study; relative aerobic strain; relative oxygen uptake reserve